PJMHS 2022
DOI: 10.53350/pjmhs22162583
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perception towards Recently Introduced Problem-Based Learning in Surgery Module: A Case of University of Ha’il

Abstract: Background: In literature, problem-based learning is repeatedly conveyed in relation to medical basic sciences. It has been introduced in the syllabus of the surgery module very recently. Aim: To assess students' perceptions towards PBL in the clinical years course of their medical study, in a surgery module. Methods: A cohort study involves the 6th year students (academic year, 2019-2020) in their surgical course at the end of the newly introduced PBL sessions using a self-administered validated questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The students in this study agreed that PBL improves their self-directed learning. This was consistent with previous research (27,28). Several studies have shown that there is no complete agreement on the validity of PBL in the development and advancement of self-learning abilities (29).…”
Section: Discussionsupporting
confidence: 92%
“…The students in this study agreed that PBL improves their self-directed learning. This was consistent with previous research (27,28). Several studies have shown that there is no complete agreement on the validity of PBL in the development and advancement of self-learning abilities (29).…”
Section: Discussionsupporting
confidence: 92%